1999
DOI: 10.1007/s001980050151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Intermittent Weekly Dose of Human Parathyroid Hormone (1-34) on Osteoporosis: A Randomized Double-Masked Prospective Study Using Three Dose Levels

Abstract: To test the effect of amino-terminal peptide 1-34 of human parathyroid hormone (hPTH (1-34)) as a possible bone anabolic agent in the treatment of osteoporosis, weekly subcutaneous injection of 50 units (L group), 100 units (M group) or 200 units (H group) of hPTH (1-34) was started in 220 patients with osteoporosis at 71 institutions randomly divided into three groups in a double-masked system. Lumbar spine bone mineral density (BMD) by dual-energy X-ray absorptiometry (DXA) increased by 0.6%, 3.6% and 8.1% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 39 publications
5
80
1
1
Order By: Relevance
“…Onceweekly administration of PTH(1-34) was shown previously to significantly increase bone mass in postmenopausal women with osteoporosis [21]. In that study, 100 and 200 units of PTH induced 3.6% and 8.1% increases in vertebral BMD, respectively, after 48 weeks of treatment.…”
Section: Ios II ' Stor I[mai*in Imentioning
confidence: 96%
“…Onceweekly administration of PTH(1-34) was shown previously to significantly increase bone mass in postmenopausal women with osteoporosis [21]. In that study, 100 and 200 units of PTH induced 3.6% and 8.1% increases in vertebral BMD, respectively, after 48 weeks of treatment.…”
Section: Ios II ' Stor I[mai*in Imentioning
confidence: 96%
“…Thus, daily nasal spray of PTH(1-34) gives a short Tmax, which increases bone formation markers and at the same time reduces bone resorption markers with net positive effect [35]. Similarly, weekly subcutaneous injections of PTH(1-34) causes an increase in bone formation markers with a reduction in bone resorption markers [36]. In contrast, although PTH-Fc fusion protein shows a long half-life, weekly or twice-weekly administration can give net anabolic effect on bone [37].…”
Section: Pth and Bone Formationmentioning
confidence: 99%
“…A sham operation was conducted on animals in one group (SHAM), whereas all animals in the remaining three groups had both ovaries surgically removed 1 week before starting treatment (OVX groups). Two OVX groups were subcutaneously administered once-weekly hPTH(1-34) acetate (Asahi Kasei Pharma Corp., Tokyo, Japan), relative activity 3,300 U/mg [4], at doses of 1.2 μg/kg (low-PTH group) or 6.0 μg/kg body weight (high-PTH group). The administration was initiated immediately after the operation.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Daily selfadministered subcutaneous injection of human PTH (hPTH) (1-34) (teriparatide) increased bone mineral density (BMD) compared to a placebo in post-menopausal osteoporotic patients [3]. Fujita et al [4] reported in a multicenter clinical trial that once-weekly administration of hPTH (100 and 200 U/week) for 12 months in patients with osteoporosis significantly increased lumbar BMD by up to 3.6% and 8.1%, respectively, without increasing bone resorption.…”
Section: Introductionmentioning
confidence: 99%